Managing infomrality through backyard rental structures : towards a hybrid model for the City of Johannesburg - Chetty, Rodney Kevin (My University, 2017)
This study investigates the role of informal backyard dwellings amongst formal state subsidised homes as a ‘Hybrid’ solution for alternative rental tenure. It focusses on two major townships in the City of Johannesburg as the units of analysis, namely Cosmo City and Diepsloot. These two areas provide direct contrasts, namely, Cosmo City with structured backyard dwellings, and Dieploot with unstructured informal backyard dwellings. Rapid growth in backyard rental dwellings signals that informality has a purpose within the confines of formality, providing impetus for a study investigating the value of a possible hybrid model for financing or regulating backyard rental. A qualitative research design was employed, and data were collected through individual face-to-face interviews with key stakeholders in the rental housing sector. The research is descriptive and explanatory. A qualitative approach has enabled the writer to clearly articulate the feelings, emotions, attitudes, opinions and views of the participants, supporting a more nuanced investigation. The study particularly explored the main components of the functional ‘Hybrid’ model for unlocking the potential of backyard rentals in accommodating low-income groups. The results provide insights into the features of informal backyard dwellings, their manifestation in the selected townships and the drivers and conditions for a successful backyard rental strategy. Among other findings, the investigation revealed that renters are satisfied with the informal relationship they share with the landlord. It further revealed that landlords continue to invest in informal backyard rental units, and this symbiotic relationship suggests that informal subletting is here to stay. The study findings suggest that formality and informality be merged into a ‘hybrid model’, to ensure a sustainable supply of alternative rental accommodation. In the ‘hybrid model’ that the study puts forward, banks, suppliers, the City of Johannesburg and other actors can engage with landlords in low-income settlements through informal channels. This would require policy support from the City of Johannesburg in a way that enables the sustainable development of incremental backyard dwellings.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Masters of the Built Environment in Housing, 2017
Keywords: Rental housing--South Africa--Johannesburg; Landlord and tenant--South Africa--Johannesburg